DIKOTOMI ILMU PENGETAHUAN DAN IMPLIKASINYA DALAM PENDIDIKAN ISLAM - Ali Wafa; Nasrul Hadi (Fakultas Agama Islam Universitas Islam Madura, 2020)
This research is a conceptual study of the dichotomy of science. The emergence of the dichotomy of science in Islam has had a lot of negative impacts on the scientific tradition, intellectuals and the implementation of Islamic education, one of which is that Muslims only deepen or fanatical knowledge of religion and ignore science so that it affects Muslims themselves, namely far lagging behind in the fields of politics and science and technology from the Western world (Europe). This is an inverse condition for the Islamic world which in the classical period has experienced a period of glory or a golden age. Even at that time, Islamic civilization became a teacher for the world of Europe, which at that time the world of Europe was in a period of darkness. On the other hand, the impact of the dichotomy is the emergence of problems in the world of Islamic education, especially Islamic higher education, most of which still follow the Salaf scholars who, when entering the modern period, experienced a gap with the development of science and technology that has greatly influenced the civilization of adult humans this. First, the concept of the dichotomy of science. Second, the history of the dichotomy of Islamic education. Third, the development of science in Islamic education. Fourth, factors arising from the dichotomy of science in Islamic education. Fifth, the implications of the dichotomy of science on Islamic education.